Effects of glycerol on enzymatic hydrolysis and ethanol production using sugarcane bagasse pretreated by acidified glycerol solution. (September 2015) - Zhang, Zhanying; Wong, Heng H.; Albertson, Peter L.; Harrison, Mark D.; Doherty, William O.S.; O'Hara, Ian M.
Highlights: 2.0 wt% glycerol inhibited glucan digestibility by 2.0%. Up to 5.0 wt% glycerol had no effect on subsequent yeast fermentation. Glycerol is a less potent inhibitor of enzymes and yeast than ionic liquids. Pilot-scale ethanol production was demonstrated with 5.51 wt% residual glycerol. An ethanol yield of 0.142 kg/kg dry bagasse can be achieved. Abstract: In this study, for the first time the effects of glycerol on enzymatic hydrolysis and ethanol fermentation were investigated. Enzymatic hydrolysis was inhibited slightly with 2.0 wt% glycerol, leading to reduction in glucan digestibility from 84.9% without glycerol to 82.9% (72 h). With 5.0 wt% and 10.0 wt% glycerol, glucan digestibility was reduced by 4.5% and 11.0%, respectively. However, glycerol did not irreversibly inhibit cellulase enzymes. Ethanol fermentation was not affected by glycerol up to 5.0 wt%, but was inhibited slightly at 10.0 wt% glycerol, resulting in reduction in ethanol yield from 86.0% in the absence of glycerol to 83.7% (20 h). Based on the results of laboratory and pilot-scale experiments, it was estimated that 0.142 kg ethanol can be produced from 1.0 kg dry bagasse (a glucan content of 38.0%) after pretreatment with acidified glycerol solution.